Fair’s Fair: A Feministic Analysis of Kamala Das’ ‘Summer in Calcutta’: Exploring the Feminine Themes in Kamala Das' 'Summer in Calcutta' (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper is an attempt to uncover the hidden meanings of the poetry of Kamala Das from the perspective of women and from the angle of self reflections of herself in her works. This paper is a kind of exploration of her poetry. The various themes that include feminine approach, man-woman relationships, Love, lust and different threads of human life which bind two opposite sexes in one relationship. This journey in her works depict all sensory experiences which have a definite bridge between man and woman. Her writing is not only a reflection of the real society but her work gives an insight knowledge of man-woman relationships' psychology also.